UPAYA BHABINKAMTIBMAS DESA GARASSIKANG DALAM MENCEGAH PENYEBARAN BERITA HOAKS PERSPEKTIF SIYASAH SYAR'IYYAH - Adityawarman, Adityawarman; Syamsuddin, Darussalam (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
This study aims to provide an overview of how the efforts of Bhabinkamtibmas of Garassikang Village, Jeneponto Regency, in preventing the spread of hoax news. This research is a qualitative research. The efforts of Bhabinkamtibmas of Garassikang Village, Jeneponto Regency in preventing the spread of hoax news are carried out through a humanist persuasive approach. Persuasive-humanist steps are chosen by considering the condition of the community which still tends to prioritize customary law to solve a problem. The Quran has ordered tabayyun of any information obtained as a verifiable effort and to prevent the spread of news containing slander (hoaxes), so that the prevention of the spread of hoax news is not only the responsibility of Bhabinkamtibmas and the government, but is a shared responsibility.